2020
DOI: 10.3390/foods9020202
|View full text |Cite
|
Sign up to set email alerts
|

Attitudinal Determinants of Beef Consumption in Venezuela: A Retrospective Survey

Abstract: Consumer surveys were conducted in the Western, Central, and Eastern regions of Venezuela to determine buying expectations, motivations, needs, perceptions, and preferences of beef consumers, and their acceptance of domestic (and foreign) beef, as affected by different intrinsic and extrinsic factors. Data (n = 693) were gathered by face-to-face interviews on the way out of fresh markets, butcher stores, supermarkets, and, in some cases, at home by using a 45-question structured questionnaire. Responses were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0
4

Year Published

2020
2020
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 22 publications
0
9
0
4
Order By: Relevance
“…The authors found that flavor was the largest contributor to satisfaction in comparison to tenderness or juiciness, accounting for 59% of the overall rating. The results also indicate that age, income, and gender influenced satisfaction [11].…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…The authors found that flavor was the largest contributor to satisfaction in comparison to tenderness or juiciness, accounting for 59% of the overall rating. The results also indicate that age, income, and gender influenced satisfaction [11].…”
mentioning
confidence: 72%
“…Arenas de Moreno [11] conducted surveys in three regions of Venezuela to determine buying expectations, motivations, needs, perceptions, and preferences of beef consumers, and their acceptance of domestic and foreign beef. Their results show that two factors explain 74% of the common variance in beef consumption.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Las características intrínsecas valoradas por los consumidores en el presente estudio, están en concordancia con los atributos intrínsecos de la carne informados por consumidores italianos [30], americanos [31] y mexicanos [11]. Entre estos atributos, el color de la carne y la pérdida de agua han sido informados como las primeras características que usa el consumidor para valorar la frescura del producto [1] y la terneza o suavidad, como uno de los factores más determinantes en la elección de la carne [32].…”
Section: Percepción Intrínseca Y Extrínseca De La Carneunclassified
“…Sin embargo, está bien documentado el efecto positivo de los cambios bioquímicos y estructurales de la maduración en la palatabilidad (terneza, jugosidad y sabor) de la carne [33]. Por lo cual, los resultados del presente estudio permiten plantear la pobre educación en calidad de carne del consumidor colombiano, similar al caso del consumidor venezolano descrito por Arenas-De Moreno et al [32], quienes indican que el concepto de maduración tiene mayor apropiación entre los consumidores de la región central de Venezuela (mayor preferencia y educación en calidad de carne) comparado con el consumidor de la región occidental.…”
Section: Percepción Intrínseca Y Extrínseca De La Carneunclassified